Are Obese Children Abused Children? - Priest, Maura (The Hastings Center report, 2018)
In 2010, a South Carolina mother was taken to court when her fourteen-year-old son reached 555 pounds. An article on the story reported, “His mother, Jerri Gray, lost custody of her son and is being charged with criminal neglect. Gray is facing 15 years on two felony counts, the first U.S. felony case involving childhood obesity.” If the caretakers of obese children are negligent, then they are also morally and legally blameworthy. I want to suggest, however, that important ethical differences exist between negligent or abusive caretakers and the caretakers of obese children and that these differences ought to make a moral and legal difference. The distinctions are nuanced, and the ethical pictures in cases of abuse, neglect, and obesity are far from black and white. However, the various types of harm that children face from their caretakers should be placed in neither the same ethical nor the same legal category. When children are beaten or sexually molested, the justification for taking them out of the home is clear: the caretakers are violating the rights of their children. Similarly, with neglect, caretakers are failing to provide their children the necessities to which they are entitled. The central question that I want to address in this article is whether the actions (or inaction) of caretakers that allow a child to become obese are morally or practically analogous to physical abuse or neglect. Ultimately, I will argue that parenting that allows a child to become obese is so morally different from both abuse and neglect that it is best understood as falling outside these categories altogether. This conclusion has important moral, practical, and legal implications.